PENGARUH LOAN TO DEPOSIT RATIO, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL DAN NON PERFOMING LOAN TERHADAP RETURN ON ASSET PADA PT. BANK MANDIRI (PERSERO) TBK PERIODE 2009-2017 - Nur Salma; Devi Wulandari (Jurnal Media Ekonomi (JURMEK), 2019)
This research was conducted to examine the effect of the Loan to Deposit Ratio (LDR), BOPO (Operational Opinion Costs), and Non Performing Loans (NPL), on Return on Assets (ROA). Data analysis techniques used are multiple linear regression with the least squares equation and hypothesis testing using t-statistics to test the partial regression coefficients and F-statistics to test the significance of the influence together with a significant level of 5%. In addition, a classic assumption test which includes normality, multicollinearity test, heterokedasitas test and autocorrelation test is also carried out. During the observation period shows that the research is normally distributed. Based on normality test, multicollinearity test, heterokedasitas test and autocorrelation test, there are no variables that deviate from classical assumptions. This shows the available data meets the requirements using the multiple linear regression equation model. The results of this study indicate that the LDR, BOPO and NPL variables have a simultaneous effect on ROA in the F test with a significant value of 0.00 <0.05. In the t test the results of the study show that LDR, BOPO and NPL partially have a significant effect on ROA and the three independent variables have an effect on ROA of 76.9%.